Emigration to South Africa's Mines - Robert E. B. Lucas (American Economic Review, 1987)
Temporary labor migration from five countries to South Africa's mines is examined. Emigration (a) diminishes domestic crop production in the short run; (b) enhances crop productivity and cattle accumulation through invested remittances in the long run; (c) increases domestic plantation wages. Conflicting interests thus exist between employers in the sending countries and in the mines. State intervention adopted in the sending countries includes forced labor, emigration quotas, and compulsory population relocation.